PELATIHAN MANAJEMEN KEUANGAN BAGI PENGUSAHA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI RUMAH BUMN BRI SEMARANG - Widhy Setyowati; Grace Tianna Solovida; Taufiq Andre Setiyono; Muhammad Purwanto; Rohmah Rojiyyah (Universitas YPPI Rembang, 2024)
The significant growth of Micro, Small, and Medium Enterprises (MSMEs) in Semarang City, totaling 91 thousand licensed units, plays a crucial role in job creation and income generation. However, the majority of MSMEs face challenges in financial management, particularly due to low education and a lack of financial knowledge. About 70% of MSMEs start due to economic pressures rather than innovative products or specific skills. The Financial Management Awareness for MSMEs aims to enhance business practitioners' knowledge of financial management principles, cash flow management, financial planning, cash risk management, and financial performance measurement.The implementation method involves 44 participants from BRI Incubator, focusing on financial management, marketing, and business strategy training. The training took place on September 18, 2023, at the BRI State-Owned Enterprise House in Semarang. The evaluation shows a significant improvement in understanding, with participants stating the usefulness of overcoming financial challenges. This activity successfully empowered MSMEs, supported local economic growth, and created a positive impact on the community. The conclusion suggests recommending group mentoring tailored to business fields to enhance the specificity of financial reports.Keywords: Community Service, Financial Management, SMEs, BRI Incubator Training